Fishflies - Lemire, Jeff (Image Comics, 2025)
A small town crime sets off a chain of events that will permanently alter the lives of several residents of bucolic Belle River, Ontario. As the manhunt heats up, a lonely girl named Franny Fox forms an unlikely friendship with a fugitive that leads them both on an odyssey of discovery and redemption... a journey that also uncovers dark secrets from the town's eerie past.